TRANSFORMATION OF THE FINANCIAL MANAGEMENT SYSTEM OF SEKAA TRUNA TRUNI: (STUDY AT SATYA MANDALA GIRI COLLEGE OF SCIENCES, GITGIT VILLAGE) - Asih, Ni Putu Erni Asih; Kurniawa, Putu Sukma; Atmaja, I Made Dwita (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study examines the transformation of the financial management system at Sekaa Truna Truni (STT) Satya Mandala Giri in Gitgit Village as a response to the increasing demands for accountability and transparency in traditional youth organizations. The underlying phenomenon is the lack of documented and transparent financial recording systems in many STTs, raising questions about how the process of adapting to a more modern financial system can occur in such a traditional structure. The novelty of this study lies in revealing the gradual process of change from manual recording to a combination of manual and digital systems, which has not been widely studied in the context of Balinese traditional organizations. This study uses a descriptive qualitative approach with interview techniques, observation, and documentation of STT administrators as well as analysis of available financial documents. The results of the study show that the transformation of the financial management system was carried out in stages, starting from simple recording to the use of Excel, as well as the integration of social media as a means of reporting to members. In conclusion, this transformation creates a financial system that is more transparent, accountable, and adaptive to technology, while still maintaining local values ​​such as ngayah and deliberation. The implication is that this model can be an example for other indigenous youth organizations in developing a modern financial management system without abandoning local wisdom.